Engaging Spinal Networks to Mitigate Supraspinal Dysfunction After CP - Edgerton, V. Reggie; Hastings, Susan; Gad, Parag N. (Frontiers in Neuroscience, 2021)
Although children with cerebral palsy seem to have the neural networks necessary to generate most movements, they are markedly dysfunctional, largely attributable to abnormal patterns of muscle activation, often characterized spasticity, largely reflecting a functionally abnormal spinal-supraspinal connectivity. While it is generally assumed that the etiologies of the disruptive functions associated with cerebral palsy cab be attributed primarily to supraspinal networks, we propose that the more normal connectivity that persists between peripheral proprioception-cutaneous input to the spinal networks can be used to guide the reorganization of a more normal spinal-supraspinal connectivity. The level of plasticity necessary to achieve the requited reorganization of within and among different neural networks can be achieved with a combination of spinal neuromodulation and specific activity dependent mechanisms. By engaging these two concepts, we hypothesize that bidirectional reorganization of proprioception-spina cord-brain connectivity to higher levels of functionality can be achieved without invasive surgery.